Evaluasi Cepat Struktur Portal Beton Bertulang Terhadap Gempa - Muttaqin, Muhammad Akbar; Yuniarto, Enno; Hendri, Andy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Earthquakes from 2004 to 2009 in Indonesia has resulted in many deaths and the collapse of the building. The American Society of Civil Engineers (ASCE) with the Federal Emergency Management Agency (FEMA) has published FEMA 310 as a handbook for seismic evaluation of buildings. FEMA 310 evaluation includes evaluation of phase one, two and three. Evaluation of phase one (tier 1) using a checklist of structural, non-structural, region of low sismicity and also geologic site hazard and foundation. Evaluation of the second phase (tier 2) is a linear analysis for structures such as static equivalence analysis and dynamic. Evaluation of the third stage (tier 3) is non- linear analysis of such a pushover. If the evaluation phase of the assessment does not meet the criteria, then it should proceed to the second phase, as well as for further evaluation. The building is located in the city of Pekanbaru that is reviewed and evaluated up to the second phase. Calculation of seismic shear force have used seismic hazard map of Indonesia has been published in 2010. This is one step to improve the performance of structures to resist earthquakes, it is expected that this will reduce structural damage and avoid loss of life. The results of the evaluation phase one (tier 1) that has been conducted shows that the buildings that were reviewed non- compliant for weak story and soft story. Evaluation of the second phase (tier 2) shows that all the columns in buildings were able to bear the load, while some beam were over strength, however both of building can be declared the buildings are safe against earthquakes (compliant).Keywords : Earthquake, FEMA 310, quick assessment, seismic evaluation